Antitumor effect of toosendanin on oral squamous cell carcinoma via suppression of p-STAT3 - Ye Wu; Lingling Chen; Cheng Feng; Tao Wang; Shaohai He; Dali Zheng; Lisong Lin (BMC, 2023)
Abstract Background Toosendanin (TSN) exhibits potent antitumor activity against various tumor cell lines. However, its efficacy against oral squamous cell carcinoma (OSCC) remains unknown. Here, we investigated the effects of TSN on OSCC cells in vitro and verified them in vivo using a patient-derived xenograft (PDX) model. Methods The effect of TSN on OSCC cells was investigated by cytotoxicity assays and flow cytometry. The expression of proteins was detected by western blotting. An OSCC PDX model was constructed to further investigate the role of TSN in regulating the function of OSCC. Results The cell viability of CAL27 and HN6 cells decreased as the concentration of TSN increased within the experimental range. Compared with controls, TSN at lower doses inhibited cell proliferation and induced apoptosis through S-phase cell cycle arrest. TSN inhibited OSCC cell proliferation by downregulating the STAT3 pathway through the inhibition of STAT3 phosphorylation. After successful construction of the OSCC PDX model with high pathological homology to the primary tumor and treatment with an intraperitoneal injection of TSN, we showed that TSN significantly reduced the tumor size of the PDX model mice without obvious toxicity. Conclusions Both in vitro and in vivo, TSN significantly inhibits the proliferation and promoted apoptosis of OSCC cells. Furthermore, TSN demonstrates potent inhibition of STAT3 phosphorylation, indicating its potential as a promising therapeutic agent for OSCC. Therefore, TSN holds great promise as a viable drug candidate for the treatment of OSCC.